The Effect of Warm Water Foot Soaking Therapy and Hand Massage on Blood Pressure and Anxiety in Hypertensive Patients - Takumasang, Reza Resaldi; Iswanti, Dwi Indah; Widiyaningsih, Widiyaningsih; Gero, Sabina (ProNers, 2025)
Background: Hypertension is a widely recognized cardiovascular disease where patients' blood pressure rises above normal levels. Hypertension is also known as a "silent killer" because its symptoms only become apparent when complications occur. There are several management approaches for hypertension patients, both pharmacological and non-pharmacological, such as those implemented by researchers who provided warm water soaking and hand massage. Objective: To determine the effect of warm water foot soaking therapy and hand massage on blood pressure and anxiety in hypertensive patients and to compare the effectiveness between the two interventions. Methods: The research design used in this study was quasi-experimental with a pre-post design with control group approach. The sampling technique used was purposive sampling with a sample size of 48 respondents divided into 2 groups. Results: Differences in blood pressure before and after hand massage in the working area of Kombos Primary Health Center, Manado City, showed a p-value of 0.000, and there was a significant difference in blood pressure before and after warm water foot soaking therapy with a p-value of 0.000. Additionally, there was a difference in effectiveness between warm water foot soaking therapy and hand massage therapy with a p-value of 0.001. Conclusion: Foot soaking therapy using warm water and hand massage have an effect in reducing blood pressure in patients with hypertension.